Evaluating social and behavioural change communication: the Soul City example: El caso de Soul City - Weiner, Renay; Goldstein, Sue; Scheepers, Esca (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
Soul City is a South African non-governmental organisation that uses edutainment, social mobilisation and advocacy to influence social and behaviour change. Established in 1992, the organisation is committed to measuring reach and impact of its activities on health and development. By referring to key public health examples, particularly HIV prevention and domestic violence, we describe the Soul City experience of evaluating complex interventions at multiple levels over time. Specific attention is given to the evaluation of Soul City’s media and social mobilisation programmes, and key findings are presented. We conclude that there is strong evidence for substantial reach and impact of Soul City on a range of desired outcomes. Important areas identified to ensure innovation and improvement going forward include using participatory methodologies, integrating qualitative and quantitative methodologies better, capturing community and collective constructs better and ensuring the integration of different methods of analysis, such as complex analyses.